Oxygenation of the Gulf of Mexico thermocline linked to the detachment of Loop Current eddies - Quintanilla, Jose Gerardo; Herguera, Juan Carlos; Sheinbaum, Julio (Frontiers in Marine Science, 2024)
This study presents oxygen data from the Gulf of Mexico (GoM) deep-water region for the period 2010–2019 collected from six oceanographic cruises and two BioARGO buoys and compares them to historical measurements. These observations link the interannual variability of the oxygen concentrations in the main thermocline waters to the frequency of Loop Current eddy (LCE) detachments. These eddies introduce significant volumes of relatively oxygen-rich waters from the Caribbean into the Gulf’s interior, thereby ventilating the main thermocline waters of the basin. Oxygen concentrations [O2] observed after periods of more than a year without LCE detachments consistently show a significant decrease in [O2] in the GoM thermocline waters. Using the oxygen measurements and altimetry data, we developed a simple box model that reproduces the oxygen variability in the GoM thermocline considering only LCE detachment area and frequency as variables, keeping all other sources of variability constant in the model. Our model successfully reproduces the observed oxygen variability in the main thermocline waters, highlighting the LCE detachment variability as a key process in the ventilation of the GoM mid-depth waters. According to our model, an average detached LCE area of approximately 97,000 km2 per year is needed to maintain oxygen levels in the thermocline waters above 2.6 ml mL L−1 in the upper thermocline and 2.4 ml mL L−1 in the lower thermocline. One further implication of this model is that if the yearly trend of decreasing detachment area of the LCEs continues in future years, oxygen concentrations in the GoM thermocline may continue to fall, potentially leading to unknown consequences for the ecological web structure at these depths.